The effect of game-based learning on performance and motivation of university students: An exploratory study - Liew, Vui Seong; Ting, Man Ling; Zou, Cheng (2023)
This study aimed to explore the impact of Game-Based Learning (GBL) on student performance and motivation in an educational setting. Our hypothesis is that GBL would lead to a significant difference in performance and positively influence motivation compared to traditional learning methods. The research employed an experimental design, utilizing a random sampling method to select participants from selected universities. Data gathering procedures involved using convenience sampling and purposive sampling methods. The sample size consisted of 36 participants, with data collected through a pre-and post-test and a motivation scale. The study targeted undergraduate students for data collection as they are potentially open to innovative learning methods. Contrary to the hypothesis on performance, there were no significant differences between the GBL and control groups. One of the reasons is that there may be a demographic reason like gender that affects the performances. Despite no significant performance differences between the GBL and control groups, the positive impact of GBL on motivation was evident, enhancing students' competence, autonomy, and relatedness. We aim to develop and implement educational curricula that promote diverse approaches for better learning experiences. The study recommends conducting longitudinal research to examine performance further and validate a new motivation scale. Similarly, it is also recommended to study individual differences to tailor the education intervention better.